Engagement of early career researchers in collaborative assessments of IPCC reports: achievements and insights - Moreno-Ibáñez, Marta; Casado, Mathieu; Gremion, Gwenaëlle; Rabanal, Valentina; Adojoh, Onema; Anoruo, Chukwuma; Arshad, Adnan; Bahar, Faten Attig; Bello, Cinthya; Bergstedt, Helena; Caccavo, Jilda Alicia; Champollion, Nicolas; et al. (Frontiers in Climate, 2024)
The participation of a diverse –in terms of geography, discipline and gender– group of Early Career Researchers (ECRs) in the peer review process can help alleviate the workload of senior researchers and counteract the perceptual biases that the latter tend to show. Moreover, ECRs can benefit from developing skills that are often not included in educational programs. From 2018 to 2021, the Association of Polar Early Career Scientists, in collaboration with other associations, organized six group reviews of the Intergovernmental Panel on Climate Change (IPCC) reports by a total of more than 600 ECRs from over 70 different countries. This study aims to evaluate this group review in terms of its contribution to the production of scientific knowledge, and as a career development opportunity for ECRs. The data analyzed consists of application forms, review comments, and feedback surveys that were collected during each review process. The results of this study show that, overall, the group reviews were a success in terms of the experience of ECRs and their contribution to the peer review of the IPCC reports. Most survey respondents considered the general organization of the group reviews satisfactory and expressed interest in participating in future group reviews. However, most participants did not engage in discussions with their peers, which constitutes a missed opportunity to engage in active learning and the shared production of knowledge. ECRs made a significant contribution to the review of the IPCC reports by producing an average of 2,422 ± 532 comments per group review, 36% of which were substantive. PhD students were shown to be as proficient reviewers as postdoctoral researchers and faculty reviewers. More importantly, the diversity of reviewers in terms of geography and discipline, together with the fact that they are ECRs, can help produce more balanced scientific reports since they bring new perspectives, thus counteracting the biases that senior researchers have. These group reviews could be improved by providing more comprehensive training and facilitating communication among reviewers so that they can engage in meaningful exchanges. We conclude that the IPCC should formalize the inclusion of ECRs in future reviews of the IPCC reports.